Implementation of Educative Learning Media Counting Tree to Improve Student's Cognitive Abilities in Kartika Tanjung Morawa Kindergarten - Dwi Novita Sari (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2021)
Counting is a branch of mathematics which is a basic skill that children need to master from an early age. In fact, the ability to count in early childhood is still very low, this is because children find it difficult to count or pronounce a sequence of numbers, count by pointing at objects and pointing to a sequence of objects. On the other hand, teachers do not take advantage of the learning media used to support children's learning outcomes in arithmetic. To overcome this problem, learning to count is carried out using educational learning media Counting Tree because by utilizing educational learning media Counting Tree (counting tree) learning to count will be easier, interesting and fun for children. This study aims to describe the implementation of learning by applying the Counting Tree educational learning media to improve the cognitive abilities of students in Kartika Tanjung Morawa Early Childhood Education. Classroom Action Research with a qualitative approach consisting of three cycles. With the research instrument used was a test of mathematical problem solving abilities. The target output to be achieved in this study is an international journal.